EFFECTIVENESS OF ACTIVE LEARNING MODEL THREE STAGE FISHBOWL DECISION TYPE TOWARDS LEARNING INDEPENDENCE OF JUNIOR HIGH SCHOOL STUDENTS IN SOCIAL STUDIES LEARNING - Siska Widya Lestari; Tetep; Eldi Mulyana; Alni Dahlena (Journal Civics And Social Studies, 2024)
Social studies is still considered a boring subject, which has an impact on students' low learning independence. Weak learning independence in students is caused by the learning models applied by educators which are less varied, thus affecting the desire to learn, sense of responsibility, self-confidence and initiative to take part in lessons. One effort to overcome this problem requires innovation and new breakthroughs in packaging or delivering social studies subject matter to students so that learning activities become more effective, one of which is by using active learning type three stage fishbowl decision. The aim of this research is to determine the effectiveness of active learning with the three stage fishbowl decision type on the learning independence of junior high school students in social studies learning and to determine the increase in learning independence among students with the active learning model with the three stage fishbowl decision type. This type of research uses a quantitative approach with a quasi-experimental method with a non-equivalent control group pretest and posttest design. The population of this research was class VIII students at SMPN 3 Garut. Samples were taken using a purposive sampling technique with 1 experimental class and 1 control class. The instruments used in this research were test question sheets, observation sheets, and questionnaires. Based on the results of the research conducted, the initial abilities of the two groups resulted in the same abilities. Meanwhile, for the final test results, the Asymp.Sig.2-tailed value was 0.000 and α was 0.05, meaning 0.000 < 0.05, so the HO was rejected. It can be concluded that there are significant differences or learning using an effective model to apply. Students' independent learning towards the three stage fishbowl decision type active learning model used in the experimental class produced a very good response. Increased learning independence of students in each indicator amounted to 1046 Desire/desire to learn, 905 initiative, 888 self-confidence, and 615 responsibility very well.